EXPERIMENTAL INVESTIGATION OF THE EFFECTS OF PRESSURE ON THE MECHANICAL, THERMAL AND MICROSTRUCTURAL PROPERTIES OF CLAY-BASED GEOPOLYMERS - Saleemullah,; Ameer Hamza,; Asma Qayoom,; Muhammad Yousaf Raza Taseer,; Syed Muhammad Shakir Bukhari,; Muhammad Naveed Khalil, (Spectrum of Engineering Sciences, 2025)
This study reveals that compaction pressure has a strong and positive effect on the mechanical and microstructural properties of clay-based geopolymers. Using naturally available clays from Cherat and Gilgit-Baltistan, activated with a 10M sodium hydroxide solution, geopolymer samples were successfully developed and tested under controlled conditions. The compressive strength results showed a clear trend: as the applied pressure increased from 5000 to 24,000 pounds, the strength of the geopolymer also improved, reaching up to 48.10 N/mm². This strength is almost four times higher than that of traditional fired clay bricks commonly used in local construction. XRD analysis confirmed that pressure promoted the formation of new crystalline compounds such as natrosilite, sodium acetate hydrates, and sodium hydrogen silicate, which are associated with stronger geo-polymeric bonding. SEM images further supported these findings by showing a progressive reduction in porosity and an improvement in particle bonding and matrix formation as pressure increased. The overall performance of the samples prepared under higher pressure was clearly superior in terms of strength and structural integrity. These results show that applying compaction pressure is a practical and effective method to improve the quality of geopolymer materials without the need for high-temperature processing. In the future, research can be extended to study the long-term durability, shrinkage behavior, water resistance, and thermal insulation properties of these materials. Additionally, combining different clays, using alternative alkali activators, or applying pressure in combination with mild heat curing may further enhance their properties and promote their adoption in sustainable construction applications.